由PSENEN始祖突变引起的结合了化脓性汗腺炎与道林‐德戈斯(Dowling–Degos)病的表现型. (14th February 2018) - Pavlovsky, M.; Sarig, O.; Eskin‐Schwartz, M.; Malchin, N.; Bochner, R.; Mohamad, J.; Gat, A.; Peled, A.; Hafner, A.; Sprecher, E.
Abstract : Linked Article: Pavlovsky et al. Br J Dermatol 2018;178 :502–508